DETERMINING EFFECTS OF HEAT TRANSFER FINS ON THE SOLIDIFICATION PROCESS OF PCM AND NANO-PCM WITH A RECTANGULAR COOLER - Kok, Besir; Gürtürk, Mert (My University, 2019)
In this study, the performances of the heat transfer fins during thesolidification processes of PCM and nano-PCMS(Al2O3 - CuO) wereinvestigated. These two situations were considered for both with and withoutfins. Two different heat transfer fins were considered in the study. Theinvestigation was carried out using both experimental (for Base-PCM) andnumerical methods. The results showed that the effects of heat transfer finswere limited due to the overcooling effect of PCMs. The solidification processof Base-PCM in the heat storage tank ended in 10 minutes, while thesolidification time of the PCM was determined as 11 minutes by using the Fin1 design. The solidification process in the heat storage tank with nano-PCM(CuO) was realized in 13 minutes with the Fin 1 design.
Keywords: Mühendislik; Makine